Exercise Motivations, Barriers, and Preferences of Tahfiz Students: A Qualitative Study - Ibrahim, Farah Wahida; Mat Ludin, Arimi Fitri; Marzuki, Nur Aqilah; Ishak, Ismarulyusda; Othman, Mohd Sham; Abdul Warif, Nor Malia; Md. Zahir, Mohd Zaharen; Yaacob, Muhamad Toriq (Makara Journal of Health Research, 2022)
Background: In Malaysia, the increasing prevalence of physical inactivity is alarming. The effects of adopting a sedentary lifestyle have led to health problems such as coronary heart disease and type II diabetes mellitus, as well as increased mortality rates. Young adults, including tahfiz students, tend to be physically inactive due to much time spent sitting during lectures or studying. Therefore, an active lifestyle must be encouraged. This study aims to identify the factors that influence tahfiz students to exercise. Methods: Data from 12 male and 19 female students were collected through in-depth interviews, which were recorded and transcribed into text then subjected to thematic analysis. Results: Results show that the main motivations to exercise were body health and fitness, self-appearance, and sense of togetherness. The main themes for barriers were aversion to exercise time and commitment. In general, respondents preferred a moderate, 10–30 minute group sessions for 3–5 times per week. Conclusions: This study revealed five themes for motivations (body health and fitness, psychological wellbeing, appearance, physical support, and enforcement), and six themes for barriers to exercise (aversion to exercise, time, commitment, discomfort, no motivation, and the environment). These factors could be considered in exercise module development to improve students’ engagement.